SUFISM AND TEACHER IN THE PERSPECTIVE OF SULUK THE PEACE OF LIFE SUNAN BONANG - Fatchullah Zarkasi (International Conference on Social and Islamic Studies, 2021)
In the book Al arba'in fi ushul al din it is said that perfect happiness is happiness that includestwo dimensions, namely the world dimension and the hereafter dimension. Happiness in theworld can be felt with a peaceful soul. Happiness in the afterlife is the happiness of meeting andcommunicating with Allah (Ahmad Faizur Rosyad, Pole: 2004) (Zaairul, 73) . In Man's searchfor Meaning, Dr. Viktor E. Frankl, professor of psychiatry at the University of Vienna wrote,“Man's search for meaning in life is the main force in his life and is not a secondaryrationalization of instinctual movement” (J. Maurus, Cinta Pena:2005). Achieving happiness andpeace of mind is actually not as simple as we think. Why is that ? Because to achieve it requiresa series of efforts that always consider the needs, risks, and the sense of value created. Even thenatural potential that we have, such as our psyche and our organs, is also taken intoconsideration.